It is currently 19 Oct 2017, 15:09

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

M03 #19

Author Message
Manager
Joined: 01 Apr 2006
Posts: 179

Kudos [?]: 130 [1], given: 0

Show Tags

15 Sep 2008, 12:36
1
KUDOS
1
This post was
BOOKMARKED
$$a$$ , $$b$$ , and $$c$$ are integers. Is $$abc = 0$$ ?

1. $$a^2 = 2a$$
2. $$\frac{b}{c} = \frac{(a+b)^2}{a^2+2ab+b^2} - 1$$ ( $$a \ne -b$$ and $$c \ne 0$$ )

[Reveal] Spoiler: OA
B

Source: GMAT Club Tests - hardest GMAT questions

REVISED VERSION OF THIS QUESTION IS HERE: m03-70290.html#p1228282

Kudos [?]: 130 [1], given: 0

CIO
Joined: 02 Oct 2007
Posts: 1218

Kudos [?]: 979 [1], given: 334

Show Tags

25 Sep 2008, 14:04
1
KUDOS
Hi.
From S1 we see that a is either 0 or 2. Insufficient.
S2. You have to notice that we need to simplify the fraction in S2:
$$\frac{b}{c} = \frac{(a+b)^2}{a^2+2ab+b^2} - 1$$
$$\frac{b}{c} = \frac{(a+b)^2}{(a+b)^2} - 1$$
$$\frac{b}{c} = 1 - 1 = 0$$
$$b = 0$$

Hope this helps.
_________________

Welcome to GMAT Club!

Want to solve GMAT questions on the go? GMAT Club iPhone app will help.
Result correlation between real GMAT and GMAT Club Tests
Are GMAT Club Test sets ordered in any way?

Take 15 free tests with questions from GMAT Club, Knewton, Manhattan GMAT, and Veritas.

GMAT Club Premium Membership - big benefits and savings

Kudos [?]: 979 [1], given: 334

Intern
Joined: 26 Apr 2010
Posts: 5

Kudos [?]: 13 [0], given: 1

Show Tags

17 May 2010, 07:24
nshah12 wrote:
Can some one explain Statement 1? Thanks!

Statement one is saying that the square of A is equal to 2 x A. So this can be 2 or 0.

0 squared = 0 * 0 = 0
2 * 0 = 0

AND

2 squared = 2 * 2 = 4
2 * 2 = 4

So statement implies that A is either 0 or 2, therefore we can't tell if ABC = 0.

Hope that helps.

Kudos [?]: 13 [0], given: 1

Manager
Joined: 15 Apr 2010
Posts: 190

Kudos [?]: 18 [0], given: 29

Show Tags

17 May 2010, 18:26
this is how I approached it:

1) First condition gives us 2 possible values of a => a=0 or 2

2) Second condition comes as [b][/c] = 1-1=0

since "c" is not = 0, "b" is zero to make the result "0". hence B is the answer!

Kudos [?]: 18 [0], given: 29

Intern
Joined: 11 Jan 2010
Posts: 38

Kudos [?]: 54 [0], given: 9

Show Tags

18 May 2010, 09:06
Question: Is abc = 0?

Solution 1:
a^2 = 2a => a . (a-2) = 0 => a = 0 or a = 2

When a = 0 => abc = 0
When a = 2 => abc may or may not be zeros depending on the values of b and c.

Thus, solution 1 does not give a clear yes or no answer and is not sufficient.

Solution 2:
Solving the given equation: a^2 + 2ab + b^2 = (a + b)^2
Thus, b/c = 1 - 1 = 0
=> b = 0

When b = 0 => abc = 0
Thus, Solution 2 gives a clear answer that, yes, abc = 0.

Therefore, the correct answer choice is B.

Award me with Kudos+1, if this helps!! Cheers!!!

Kudos [?]: 54 [0], given: 9

Director
Joined: 21 Dec 2009
Posts: 582

Kudos [?]: 831 [0], given: 20

Concentration: Entrepreneurship, Finance

Show Tags

18 May 2010, 10:24
Enough solution has been given from the previous posts.
(1) a= 0 or 2...insufficient
(2) b=0...sufficient to answer whether abc = 0 (yes).
B, off course is the answer.
_________________

KUDOS me if you feel my contribution has helped you.

Kudos [?]: 831 [0], given: 20

Manager
Joined: 27 May 2010
Posts: 197

Kudos [?]: 71 [0], given: 3

Show Tags

22 Aug 2010, 05:47
A is insufficient as a=2 and B & C values are not given
B is sufficient because b/c = 1-1 => 0

Since c cannot be zero, b = 0 ==> abc=0

Kudos [?]: 71 [0], given: 3

Director
Joined: 01 Feb 2011
Posts: 726

Kudos [?]: 143 [0], given: 42

Show Tags

19 May 2011, 05:57
1. Not sufficient
As a can be 0 or 2,abc may or may not be 0.
2.Sufficient
b/c = 1-1 = 0.
=> b=0=> abc=0

Posted from my mobile device

Kudos [?]: 143 [0], given: 42

Manager
Joined: 15 Apr 2011
Posts: 63

Kudos [?]: 8 [0], given: 2

Location: Bangalore India
Schools: LBS, HBS, ISB, Kelloggs, INSEAD

Show Tags

19 May 2011, 21:22
jjhko wrote:
$$a$$ , $$b$$ , and $$c$$ are integers. Is $$abc = 0$$ ?

1. $$a^2 = 2a$$
2. $$\frac{b}{c} = \frac{(a+b)^2}{a^2+2ab+b^2} - 1$$ ( $$a \ne -b$$ and $$c \ne 0$$ )

[Reveal] Spoiler: OA
B

Source: GMAT Club Tests - hardest GMAT questions

Can't seem to figure out the explanation that I saw on the test.

Thanks,
John.

I think the answer is B as st 2 gives us b=0 because $$C \ne 0$$. so abc = 0.
_________________

Thanks,
AM

Kudos [?]: 8 [0], given: 2

Manager
Joined: 11 Jul 2009
Posts: 165

Kudos [?]: 58 [0], given: 79

WE: Design (Computer Software)

Show Tags

20 May 2011, 05:47
\frac{b}{c} = \frac{(a+b)^2}{a^2+2ab+b^2} - 1 ( a \ne -b and c \ne 0 )
(a+b)^2=a^2+2ab+b^2
therefore frac{(a+b)^2}{a^2+2ab+b^2}=1
\frac{(a+b)^2}{a^2+2ab+b^2} - 1 =0
so 2 is sufficient
_________________

Kaustubh

Kudos [?]: 58 [0], given: 79

Intern
Joined: 18 May 2011
Posts: 18

Kudos [?]: 2 [0], given: 1

Show Tags

22 May 2011, 11:49
Interpretation:
Statement: a=0 or b=0 or c=0
all three a,b,c =0?

option 1: insufficient since a=0 or a=2
option 2: sufficient since b=0

Ans: B

Kudos [?]: 2 [0], given: 1

Intern
Joined: 22 May 2012
Posts: 1

Kudos [?]: [0], given: 0

Show Tags

23 May 2012, 22:13
As we know $$a^2 + 2ab +b^2$$ is$$(a+b)^2$$
Therefore the expression $$(a+b)^2/(a^2 +2ab + b^2)$$ can be reduced to 1
So substituting this in our equation we get
b/c=1 - 1 =0
which implies b=0, which satisfies our condition

Kudos [?]: [0], given: 0

Math Expert
Joined: 02 Sep 2009
Posts: 41891

Kudos [?]: 128905 [1], given: 12183

Show Tags

23 May 2013, 05:08
1
KUDOS
Expert's post
jjhko wrote:
$$a$$ , $$b$$ , and $$c$$ are integers. Is $$abc = 0$$ ?

1. $$a^2 = 2a$$
2. $$\frac{b}{c} = \frac{(a+b)^2}{a^2+2ab+b^2} - 1$$ ( $$a \ne -b$$ and $$c \ne 0$$ )

[Reveal] Spoiler: OA
B

Source: GMAT Club Tests - hardest GMAT questions

Can't seem to figure out the explanation that I saw on the test.

Thanks,
John.

BELOW IS REVISED VERSION OF THIS QUESTION:

Is $$abc = 0$$ ?

In order $$abc = 0$$ to be true at least one of the unknowns must be zero.

(1) $$a^2 = 2a$$ --> $$a^2-2a=0$$ --> $$a(a-2)=0$$ --> $$a=0$$ or $$a=2$$. If $$a=0$$ then the answer is YES but if $$a=2$$ then $$abc$$ may not be equal to zero (for example consider: $$a=2$$, $$b=3$$ and $$c=4$$). Not sufficient.

(2) $$b= \frac{(a*\sqrt{c}+b*\sqrt{c})^2}{a^2+2ab+b^2} - c$$ --> $$b= \frac{c*(a+b)^2}{(a+b)^2} - c$$ --> $$b=c-c$$ --> $$b=0$$. Sufficient.

_________________

Kudos [?]: 128905 [1], given: 12183

Intern
Joined: 20 Nov 2012
Posts: 18

Kudos [?]: 5 [2], given: 0

Location: United States
GMAT Date: 06-15-2013
GPA: 3.75
WE: Information Technology (Computer Software)

Show Tags

23 May 2013, 17:35
2
KUDOS
(A)a(a-2) = 0

a = 0 or a =2

In sufficient
b/c = ((a+b)^2 - (a+b)^2)/(a+b)^2

b/c=0

b=0

Sufficient

Ans:B

Kudos [?]: 5 [2], given: 0

Intern
Joined: 01 Mar 2013
Posts: 20

Kudos [?]: 2 [0], given: 7

Schools: HBS '16

Show Tags

24 May 2013, 21:52
guptasulabh7 wrote:
(A)a(a-2) = 0

a = 0 or a =2

In sufficient
b/c = ((a+b)^2 - (a+b)^2)/(a+b)^2

b/c=0

b=0

Sufficient

Ans:B

Is this the right simplification for statement 1:-

I got only 1 value for a i.e. a=2

a square = 2a
a * a = 2a
a = 2

if its not correct simplification please explain, why?

Kudos [?]: 2 [0], given: 7

Math Expert
Joined: 02 Sep 2009
Posts: 41891

Kudos [?]: 128905 [0], given: 12183

Show Tags

25 May 2013, 03:13
crackgmat2013 wrote:
guptasulabh7 wrote:
(A)a(a-2) = 0

a = 0 or a =2

In sufficient
b/c = ((a+b)^2 - (a+b)^2)/(a+b)^2

b/c=0

b=0

Sufficient

Ans:B

Is this the right simplification for statement 1:-

I got only 1 value for a i.e. a=2

a square = 2a
a * a = 2a
a = 2

if its not correct simplification please explain, why?

Yes, that's not correct.

Never reduce an equation by a variable (or expression with a variable), if you are not certain that the variable (or the expression with a variable) doesn't equal to zero. We can not divide by zero.

So, if you divide (reduce) $$a^2=a$$ by $$a$$ you assume, with no ground for it, that $$a$$ does not equal to zero thus exclude a possible solution (notice that both $$a=2$$ AND $$a=0$$ satisfy the equation).

Hope it's clear.
_________________

Kudos [?]: 128905 [0], given: 12183

Intern
Joined: 01 Mar 2013
Posts: 20

Kudos [?]: 2 [0], given: 7

Schools: HBS '16

Show Tags

25 May 2013, 11:39
Thank you Bunuel for clarifying d doubt

Bunuel wrote:
crackgmat2013 wrote:
guptasulabh7 wrote:
(A)a(a-2) = 0

a = 0 or a =2

In sufficient
b/c = ((a+b)^2 - (a+b)^2)/(a+b)^2

b/c=0

b=0

Sufficient

Ans:B

Is this the right simplification for statement 1:-

I got only 1 value for a i.e. a=2

a square = 2a
a * a = 2a
a = 2

if its not correct simplification please explain, why?

Yes, that's not correct.

Never reduce an equation by a variable (or expression with a variable), if you are not certain that the variable (or the expression with a variable) doesn't equal to zero. We can not divide by zero.

So, if you divide (reduce) $$a^2=a$$ by $$a$$ you assume, with no ground for it, that $$a$$ does not equal to zero thus exclude a possible solution (notice that both $$a=2$$ AND $$a=0$$ satisfy the equation).

Hope it's clear.

Kudos [?]: 2 [0], given: 7

Intern
Joined: 11 Aug 2013
Posts: 8

Kudos [?]: [0], given: 1

Concentration: Finance
Schools: Fuqua - Class of 0
GPA: 3.24

Show Tags

09 May 2014, 22:14
I have a couple of questions. I get what is done with condition 1, but with condition 2 I don't properly follow your thinking.

Could someone show me how the statement 2 is simplified (step-by-step) and how do you come up with b/c being 1-1? Am I missing something basic here?

Thanks!

Posted from my mobile device

Kudos [?]: [0], given: 1

Math Expert
Joined: 02 Sep 2009
Posts: 41891

Kudos [?]: 128905 [0], given: 12183

Show Tags

10 May 2014, 05:50
financebunny wrote:
I have a couple of questions. I get what is done with condition 1, but with condition 2 I don't properly follow your thinking.

Could someone show me how the statement 2 is simplified (step-by-step) and how do you come up with b/c being 1-1? Am I missing something basic here?

Thanks! :)

Posted from my mobile device

(2) $$b= \frac{(a*\sqrt{c}+b*\sqrt{c})^2}{a^2+2ab+b^2} - c$$.

Factor out $$\sqrt{c}$$ from the numerator and apply $$a^2+2ab+b^2=(a+b)^2$$ to the denominator: $$b= \frac{c*(a+b)^2}{(a+b)^2} - c$$

Reduce by $$(a+b)^2$$: $$b=c-c$$ --> $$b=0$$. Sufficient.

Does this make sense?
_________________

Kudos [?]: 128905 [0], given: 12183

Re: M03 #19   [#permalink] 10 May 2014, 05:50
Display posts from previous: Sort by

M03 #19

Moderator: Bunuel

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.